Mental health mediators of subjective cognitive concerns among World Trade Center responders. (August 2021) - Stein, Cheryl R.; Cooney, Michael L.; Frank, Brandon; Bender, Heidi A.; Winkel, Gary; Lucchini, Roberto G.
Abstract: Decline in cognitive functioning among rescue and recovery workers who responded in the aftermath of the September 11, 2001, World Trade Center (WTC) attacks is of emerging interest. Responders are vulnerable to cognitive decline from exposure to airborne toxins present at the WTC site, as well as from WTC-related mental and physical health conditions. To better understand the relationship between occupational WTC exposure, mental health, physical health and subjective cognitive functioning, we examined the mediating role of health status in the association between exposure and subjective cognitive concerns in a multi-site, longitudinal investigation of the WTC General Responder cohort (n = 16, 380 responders; n = 58, 575 visits) for the period 2002–2015. Through latent class analyses, we identified a four-level marker of cognitive concerns based on information from a Self-Administered Mental Health Questionnaire. Using generalized linear mixed models with random intercepts, we observed that a higher intensity WTC exposure composite was associated with greater cognitive concerns, and that this association was operating almost entirely through mental health comorbidities, not physical health comorbidities. In fully adjusted models, the inclusion of probable depression, anxiety, PTSD and use of psychotropic medications attenuated the association between highest WTC exposure and greatest cognitive concerns. Physical health did not appear to be on the pathway between WTC exposure and cognitive concerns. Understanding the underlying sources of cognitive concerns may help identify vulnerable members of the General Responder cohort and potentially aid clinical decision-making, such as treatment choice and enhanced screening options. Earlier diagnosis and symptom treatment may help preserve functional independence. Highlights: Cognitive functioning among rescue and recovery workers who responded in the aftermath of the September 11, 2001 World Trade Center attacks is of emerging interest. Self-reported cognitive concerns in this population are common. Associations between greater exposure and greater cognitive concerns appear driven primarily by mental health comorbidities.